Flying J : governance through crash and takeoff - Shein, James B., 1942- ([London] : SAGE, 2016)
Flying J was a family-owned company that operated travel plazas, oil refineries, a bank for trucking companies and other related businesses. In early 2009, Crystal Call Maggelet, the majority shareholder and new CEO of Flying J, was tasked with saving the company founded by her father in 1968. This case explains how she set about salvaging the organisation, which had grown from four gas stations to become a vertically integrated $18 billion company.
Originally Published in: Shein, J. B. (2015). Flying J: Governance through Crash and Takeoff. 5-214-252. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Flying J (Firm); Crisis management -- Case studies; Bankruptcy -- United States -- Cases; Corporate governance -- Case studies